Dissection of the Regional Cities: Pryshchepa Olena. The cities of Volyn in the second half of the nineteenth and early twentieth centuries. : Review (City: History, Culture, Society, 2017)
The publication of the book was the result of the author's many years of research. The theme of the monograph is in line with the theme of the candidate's dissertation, so in front of us - an expanded and supplemented version.
Keywords: City; Volyn'; review; XIX century